2012
DOI: 10.5455/jeim.201111.or.015
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role of abdominal drainage in primarily repaired perforated peptic ulcers?

Abstract: To compare the survival and post-op complications following primary closure of perforated peptic ulcer by omental patch technique in 4 groups of patients as follows: two-drain group, one-drain subhepatic group, one-drain pelvic group and nodrain group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 33 publications
8
18
1
Order By: Relevance
“…These observations are consistent with previous reports [18]. The present study also observed one case of small intestinal obstruction (IO).…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…These observations are consistent with previous reports [18]. The present study also observed one case of small intestinal obstruction (IO).…”
Section: Resultssupporting
confidence: 94%
“…Proper and through peritoneal lavage are doing equally good as observed in this study. This finding is in agreement with previous studies [12][13][14][15][16]18].…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations